Abuse of Authority and Gratification in Customs Institutions: Juridical-Empirical Analysis of The Directorate General of Customs Officials Case in 2026 - Murwoto, Murwoto; MS Tumanggor; ST Laksanto Utomo (Jurnal Smart Hukum (JSH), 2026)
This article examines the criminal liability of officials of the Directorate General of Customs and Excise (DJBC) of the Republic of Indonesia in the context of the bribery and gratification case uncovered in February 2026. Employing a juridical-empirical (socio-legal) approach, this study analyses the fulfillment of corruption offense elements under Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 on the Eradication of Corruption, and examines the correlation between administrative discretion and abuse of authority. Data were collected through documentary research of primary legal sources, official releases of the Corruption Eradication Commission (KPK), and peer-reviewed academic literature. The results reveal that the modus operandi involved systematic manipulation of the customs inspection lane system and receipt of monthly bribes amounting to IDR 7 billion to facilitate the importation of counterfeit goods without full physical examination. Legal analysis demonstrates that the abuse of administrative discretion in determining inspection lanes constitutes a corruption offense when accompanied by receipt of gifts or promises. Theoretically, the case validates Klitgaard's (1988) corruption formula: the convergence of authority monopoly, broad discretion, and low accountability. This study further identifies systemic implications for institutional reform of the DJBC, encompassing integrity-based merit systems, transparent audit trails in customs processes, and expanded anti-corruption collaboration mechanisms